Cancer Stem Cells in Tumor Pathogenesis after Cryoablation - Goltsev, Anatoliy N.; Diabina, Olga A.; Ostankov, Maksim V.; Bondarovich, Nikolay A.; Yampolskaya, Ekaterina Ye. (Problems of Cryobiology and Cryomedicine, 2015)
The review highlights some areas of malignant tumor treatment, particularly the cryosurgery of solid tumors. There is discussed the possibility of using the method of cryoablation as a tool for targeting and inactivation of cancer stem cells, being the main structural unit, initiating, maintaining growth and tumor metastasis. The publications regarding the phenotypic and functional characteristics of tumor-inducing cells, including both more potent CSCs and advanced in the differentiation of their descendants, the nature of cold factor impact on them were analyzed. The main ways to optimize the use of cryoablation technique in clinical practice are under consideration. Probl Cryobiol Cryomed 2015; 25(3):205-218